Characterization of the hypertonically induced tyrosine phosphorylation of erythrocyte band 3. - Minetti, G (1998)
Human erythrocyte band 3 becomes rapidly phosphorylated on tyrosine residues after exposure of erythrocytes to hypertonic conditions. The driving force for this phosphorylation reaction seems to be a decrease in cell volume, because (1) changes in band 3 phosphotyrosine content accurately track repeated changes in erythrocyte volume through several cycles of swelling and shrinking; (2) the level of band 3 phosphorylation is independent of the osmolyte employed but strongly sensitive to the magnitude of cell shrinkage; and (3) exposure of erythrocytes to hypertonic buffers under conditions in which intracellular osmolarity increases but volume does not change (nystatin-treated cells) does not promote an increase in tyrosine phosphorylation. We hypothesize that shrinkage-induced tyrosine phosphorylation results either from an excluded-volume effect, stemming from an increase in intracellular crowding, or from changes in membrane curvature that accompany the decrease in cell volume. Although the net phosphorylation state of band 3 is shown to be due to a delicate balance between a constitutively active tyrosine phosphatase and constitutively active tyrosine kinase, the increase in phosphorylation during cell shrinkage was demonstrated to derive specifically from an activation of the latter. Further, a peculiar inhibition pattern of the volume-sensitive erythrocyte tyrosine kinase that matched that of p72syk, a tyrosine kinase already known to associate with band 3 in vivo, suggested the involvement of this kinase in the volume-dependent response.